The relationship between eco-tourists' organization membership, knowledge, and recycling behaviour - Karakan, Halil Ibrahim; Ertas, Cagdas (Routledge Journals, Taylor & Francis Ltd, 2025)
This study explores the relationship between ecotourists' environmental knowledge (EK) and recycling behaviour (RB) by focusing on how membership in environmental organization (EOM) influences this relationship. Data were collected from 268 ecotourists visiting Gaziantep, T & uuml;rkiye, using structured questionnaires, and were analysed using Structural Equation Modeling (SEM) and Partial Least Squares (PLS) methods via SMART PLS software. The analysis revealed a significant positive relationship between EK and RB, and found that EOM further enhances this relationship. Specifically, being part of such organizations strengthens the impact of EK on RB, suggesting that organizational involvement plays a crucial role in translating knowledge into action. These findings highlight the importance of educational and organizational strategies in fostering sustainable behaviours among ecotourists.
Keywords: Ecotourist behaviour; pro-environmental behaviour; environmental knowledge; environmental organizational membership; recycling